M.C. Higgins, the great - Hamilton, Virginia, 1934-2002. (New York : Aladdin paperbacks, 2006)
As a slag heap, the result of strip mining, creeps closer to his house in the Ohio hills, fifteen-year-old M.C. is torn between trying to get his family away and fighting for the home they love.
"25th anniversary edition"--T.p. verso.
English language and literature.
Keywords: African Americans -- Juvenile fiction; African Americans -- Fiction; Coming of age -- Fiction; Family life -- Ohio -- Fiction; Mountain life -- Ohio -- Fiction; Ohio -- Fiction